Too Fast, Too Furious? Digital Credit Delivery Speed and Repayment Rates - Alfredo Burlando; Michael A. Kuhnk; Silvia Prina (Institute of Labor Economics (IZA), 2023)
Digital loans are a source of fast, short-term credit for millions of people. While digital credit broadens market access and reduces frictions, default rates are high. We study the role of the speed of delivery of digital loans on repayment. Our study uses unique administrative data from a digital lender in Mexico and a regression-discontinuity design. We show that reducing loan speed by doubling the delivery time from ten to twenty hours decreases the likelihood of default by 21%. Our findings suggest that selectively slowing down credit could improve lender profitability and help consumers avoid default.
Keywords: D14; D18; G51; O16; 330; digital credit; waiting periods; defaults; financial access